Investigating the structural linkage between IT capability and organizational agility: A study on Indian financial enterprises. Issue 5 (12th September 2016) - Panda, Sukanya; Rath, Santanu Kumar
Abstract : Purpose: Information technology (IT) is normally regarded as an enabling factor for making firms agile. Usually, it has been realized that greater IT spending enhances a firm's agility. However, the role of IT as an obstructing factor towards organizational agility cannot be overlooked. Taking this commonly perceived but less-studied IT-agility contradiction into account, the purpose of this paper is to investigate whether IT can augment or impede organizational agility. This research which is conducted in context to privately owned Indian financial enterprises proposes the premise that effective IT resource management is imperative for organizations to thrive for greater firm-wide IT capability for enhanced agility. Design/methodology/approach: Primary data collected from 300 business and IT executives working in various privately owned financial enterprises across India are used for this study and a structural equation modelling is employed to assess the IT-agility link. Findings: The findings of the study are two-folded. First, this study concludes that IT capability acts as an enabler for business process and market responsive organizational agility. Second, if IT spending is not properly translated into creating superior capability, huge and impudent IT investments will impede the overall organizational agility. Originality/value: This paper investigates both exogenous variable (IT capability) and endogenous variable (organizational agility) in terms of second-order reflective measures and establishes a significant structural link between both the dimensions of IT capability (managerial and technical) and organizational agility (business process and market responsive). This analysis illustrates the moderating effect of IT spending on each of these relationships, thereby greatly contributes and extends the existing IT capability-agility related information systems literature.